Takayasu arteritis is characterised by disturbances of B cell homeostasis and responds to B cell depletion therapy with rituximab. Issue 1 (27th September 2011) - Hoyer, Bimba F; Mumtaz, Imtiaz M; Loddenkemper, Konstanze; Bruns, Anne; Sengler, Claudia; Hermann, Kay-Geert; Maza, Sofiane; Keitzer, Rolf; Burmester, Gerd-Rüdiger; Buttgereit, Frank; Radbruch, Andreas; Hiepe, Falk
Abstract : Introduction: Takayasu arteritis (TA) is a large vessel vasculitis involving the aorta and its major branches. T cell-mediated autoimmunity is thought to play a major role in its pathogenesis, while the role of B cells is still unclear. Methods: B cell subsets in the peripheral blood of 17 patients with TA were analysed and compared with nine patients with active systemic lupus erythematosus (SLE) and nine healthy controls by flow cytometry. Based on these findings, three patients with active refractory TA were treated with B cell depletion therapy (BCDT) using monoclonal anti-CD20 antibodies (rituximab). Results: The absolute number and frequency of peripheral blood CD19 + /CD20 − /CD27 high antibody-secreting cells in patients with active TA was significantly higher than in healthy donors. As in active SLE, the majority of these cells are newly generated plasmablasts which significantly correlated with TA activity. Three patients with active refractory TA and expansion of plasmablasts were successfully treated with BCDT, which resulted in remission. Conclusion: Disturbances of B cell homeostasis may be critical in TA. Circulating plasmablasts could be a useful biomarker of disease activity and a tool for selecting appropriate candidates for BCDT. B cells and plasmablasts/plasma cells may therefore represent novel targets for effective therapies for TA.